Salicylic acid delays pear fruit senescence by playing an antagonistic role toward ethylene, auxin, and glucose in regulating the expression of PpEIN3a - Xu, Yue; Huo, Liyue; Zhao, Keke; Li, Yawei; Zhao, Xinran; Wang, Huiying; Wang, Wenli; Shi, Haiyan (Frontiers in Plant Science, 2023)
Salicylic acid (SA) and ethylene (ET) are crucial fruit senescence hormones. SA inhibited ET biosynthesis. However, the mechanism of SA delaying fruit senescence is less known. ETHYLENE INSENSITIVE 3 (EIN3), a key positive switch in ET perception, functions as a transcriptional activator and binds to the primary ET response element that is present in the promoter of the ETHYLENE RESPONSE FACTOR1 gene. In this study, a gene encoding putative EIN3 protein was cloned from sand pear and designated as PpEIN3a. The deduced PpEIN3a contains a conserved EIN3 domain. The evolutionary analysis results indicated that PpEIN3a belonged to the EIN3 superfamily. Real-time quantitative PCR analysis revealed that the accumulation of PpEIN3a transcripts were detected in all tissues of this pear. Moreover, PpEIN3a expression was regulated during fruit development. Interestingly, the expression of PpEIN3a was downregulated by SA but upregulated by ET, auxin, and glucose. Additionally, the contents of free and conjugated SA were higher than those of the control after SA treatment. While the content of ET and auxin (indole-3-acetic acid, IAA) dramatically decreased after SA treatment compared with control during fruit senescence. The content of glucose increased when fruit were treated by SA for 12 h and then there were no differences between SA treatment and control fruit during the shelf life. SA also delayed the decrease in sand pear (Pyrus pyrifolia Nakai. ‘Whangkeumbae’) fruit firmness. The soluble solid content remained relatively stable between the SA treated and control fruits. This study showed that SA plays an antagonistic role toward ET, auxin, and glucose in regulating the expression of PpEIN3a to delay fruit senescence.